Borderlands in world history, 1700-1914
"Borderlands have loomed large in modern world history. Industrialization, the development of the modern city, faster means of communication, the spread of imperialism and the rise of the modern nation-state have meant that borderlands came to encompass and divide more people than ever before. Borderlands were worldwide phenomena in which various authoritative institutional presences -- many of them new to world history -- attempted to establish borders, thus forming the basis for a myriad of reactions, counter-reactions, and interactions. Yet the study of borderlands has largely remained confined within the circles of various regional specializations. Covering two hundred years, this groundbreaking book brings together essays on borderlands by leading experts in the modern history of the Americas, Europe, Africa, Asia and Australia to offer the first historical study of borderlands with a global reach. Comprising fifteen chapters, plus a wide-ranging introduction by the editors and specially-commissioned maps, the volume critically engages with recent research while remaining accessible to student readers."--Publisher's website.